MENINGKATKAN HASIL BELAJAR KESETIMBANGAN KIMIAMELALUI MODEL PEMBELAJARAN JIGSAW PADA SISWA KELAS XI ANK DI SMKN 5 JEMBER - M, Nurul Kartika (Jurnal Pengembangan Pendidikan, 2013)
Abstract. Chemical equilibrium is one of the materials studiedin class XI odd semester at SMK 5 Jember. To study this material, ideallystudents have to knowÂ  the concept of"molarity" which has been studied before, so inÂ  learning material "ChemicalEquilibrium" students will more quickly understandÂ  the concept not merely hear and record whatthe teacher discussed in class making them remain not understand the subjectmatter. The other problem is when they were asked to work on the exercises inthe classroom, they did not want to, they just waited for the results of thediscussion notes on the board. This made students learnt less meaningful as theparticipation of students in learning was low. Student-oriented learningmodel,"JIGSAW", was done by dividing the students into groups of peer tutoring. AfterÂ  discussing questions, a representative groupbecame tutor in classical class. Students who become tutors were required tothink ahead at a higher level to understand the essence of the subject matterso as to better understand / master the concepts of the subject matter. The scoreobtained by the tutor of each group becomes the groupâs score. It aims atincreasing the sense of belonging among the members of the group. After usingJigsaw strategy there is an increase of the studentsâ average score of 68.81into 73.65. Besides, on the basis of attitude notes and studentâs profil card,there is also improvement of students participation in the class discussion Â Keywords: Improved Learning Outcomes "EquilibriumReaction" Model Pembelajaran âJIGSAWâ